1992
DOI: 10.1007/bf01309814
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of African swine fever virus in monkey kidney cells after reversible inhibition of replication by cycloheximide

Abstract: The late cytoplasmic phases of African swine fever virus (ASFV) morphogenesis in monkey kidney cells have been studied by transmission electron microscopy, focusing attention on the synthesis of viral envelopes. Morphogenesis was studied after reversible cycloheximide blockage of monkey kidney cells infected with ASFV. ASFV appears to synthesize its external and internal envelopes within the cellular cytoplasm, at the same time as the capsid is formed, with intracellular and extracellular virions showing simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Such a model is divergent in some aspects from others previously reported. For example, Schloer (30) and Arzuza et al (2) include an additional membrane between the capsid and the external envelope. Such a membrane would be the outermost layer of the intracellular particles.…”
Section: Discussionmentioning
confidence: 99%
“…Such a model is divergent in some aspects from others previously reported. For example, Schloer (30) and Arzuza et al (2) include an additional membrane between the capsid and the external envelope. Such a membrane would be the outermost layer of the intracellular particles.…”
Section: Discussionmentioning
confidence: 99%
“…Virion morphogenesis has been examined ultrastructurally, and the functions of specific viral proteins during this process have been identified either using immunoelectron microscopy and viral mutants lacking or inducibly expressing specific viral genes Arzuza et al 1992;Breese and DeBoer 1966;Brookes et al 1996;Garcia-Escudero et al 1998;Moura Nunes et al 1975;Rouiller et al 1998). ASFV replication primarily occurs in virus factories, elements of which are first observed by 6-8 h p.i.…”
Section: Virion Morphogenesismentioning
confidence: 99%
“…The progressive assembly of capsid and matrix proteins on the cytoplasmic face of these membranes leads to the production of fully assembled icosahedral particles that appear as 200-nm hexagons in cross-sections taken through virus assembly sites (49). Following assembly, mature ASFV particles leave the factory, move through the cytoplasm, and are eventually released from the cell by budding through the plasma membrane (6). Early studies have shown that ASFV particles associate with microtubules in vitro (16), and recent works suggest that retrograde dynein-dependent microtubule transport is required for the inward movement of the virus (3,26).…”
mentioning
confidence: 99%